AcroBel – the Belgian registry on acromegaly: a survey of the ‘real-life’ outcome in 418 acromegalic subjects - Bex, Marie; Abs, Roger; T’Sjoen, Guy; Mockel, Jean; Velkeniers, Brigitte; Muermans, Katja; Maiter, Dominique (European journal of endocrinology, 2007)
Objectives: To constitute a registry on acromegaly, AcroBel, to evaluate the epidemiology and quality of care of acromegaly in Belgium and Luxembourg. Design: A nationwide survey from June 2003 till September 2004 aiming to collect data from all patients with acromegaly who had visited the participating endocrine clinics after 1 January 2000. Methods: Retrospective data collection coupled to a visit within the survey period, allowing sampling of metabolic parameters and centralised determination of GH and IGF-I. Results: Four hundred and eighteen patients (51% men) were included, of which 96 were new cases, giving a mean incidence of 1.9 cases per million (c.p.m.) per year. The global prevalence was 41 c.p.m. but varied between 21 and 61 among different areas. Twenty-eight deaths were reported at a median age of 68 years in men and 74 years in women. The standardised mortality rate was significantly increased only in irradiated patients (2.70; confidence interval 1.60–4.55). Central measurements were available in 316 (75%) patients. Mean GH was ≤ 2 μg/l in 65% and IGF-I was normal for age in 56%, while both criteria were fulfilled in 49%. Multimodal treatment was more effective than primary medical therapy, since 56.5% were controlled versus 24.3% (P < 0.0001). Conclusions: AcroBel provides an excellent tool to analyse the prevalence, incidence, treatment modalities and outcome of acromegaly in Belgium. This real-life survey reveals that only half of acromegalic patients received an adequate therapy resulting in cure or disease control when stringent biochemical criteria are used.